Assessment and monitoring of land degradation in the northwest coast region, Egypt using Earth observations data - Fawzy Hassan Abdel-Kader (Egyptian Journal of Remote Sensing and Space Sciences, 2019)
This study assesses the spatial and temporal distribution of land degradation hotspots and their driving forces in the northwest coast of Egypt (NWC) based on MODIS-Enhanced Vegetation Index (EVI) and Tropical Rainfall Measuring Mission (TRMM) satellite rainfall data, using time series analysis and binomial logistic regression methodologies. The time series analyses of rainfall TRMM data across 2001–2016 proved the inter-annual rainfall variability through northwest coast of Egypt. Year 2016 was the most wet year with ∼690 mm/year and year 2010 is the most dry one with 89 mm/year with a trend line of 150 to 300 mm. Negative trends in vegetation degradation occurred across 2001–2016 in 28–37% at NWC, Dabaa and Matrouh, but only in 13% at Barrani Areas with improvement of vegetation cover ranged between 5 and 15% at NWC, Dabaa and Matrouh and increased to 38% at Barrani. The reclassified RESTREND-human induced rainfall adjusted map gives land degradation hotspots up to about 37% of the NWC area across 2001–2016, while 27% responded to land improvement measures. About half of the land degradation area (16%) and about one tenth (9%) of the land improvement areas are statistically significant. Spatial logistic regression modeling ranked the factors influencing land degradation dynamics in Matrouh subarea in decreasing order as: elevation, slope, range land, vegetation index, negative change in vegetation index, bare land, mid-slope position, and multi resolution ridge top flatness index . Keywords: Land degradation, MODIS time series, TRMM rainfall time series, RESTREN, Northwest Coast of Egypt